(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The aim of the paper is to examine the alternativeness of the motif of the female dead beloved in Serbian literature, or to focus on female-authored texts about their deceased spouses. The research attention will be focused on the memoir texts – Savka Subotić’s About Jovan Subotić. Memoirs of his wife (O Jovanu Subotiću. Uspomene njegove žene) and on Paulina Lebl Albala’s Vid’s life (Vidov život). While male authors in thematization of this motif could extense tradition or create a polemical relationship towards tradition, female authors shaped the discourse on the death of a beloved man according to social and cultural models within which the discourse on the death of a man was constituted, independently of literary tradition. The discourse of female mourning is defined by the public sphere, given that lament is an oral genre, while the discourse on the death of a man is most often constituted through the figures of martyrs, saints, or warriors. On the other hand, when female authors reached for tradition, it was a medieval or folk literature. The strongly emphasized Christian tradition of Serbian culture, as well as the presence and cultivation of the heroic principle within it, has led to frequent discursive equalization of life and death, with death being seen as a form of new life, which is primarily related to the development and interpretation of the Kosovo legend. This context also determined the genre form, and thus, in contrast to the elegy, we have stories about men which are shaped by the discourse of female memory, which strives to give them such qualities that would make them documents worth remembering. In contrast to the medieval lament or the folk lament, the analyzed texts of the authors are more shaped by a narrative that celebrates men, which was more dominant in Serbian culture.